The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/bdra.23569
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Maternal Water Consumption and Birth Defects in the National Birth Defects Prevention Study (2000–2005)

Abstract: These analyses suggest the importance of sufficient water consumption during early pregnancy, above and beyond it being a marker of higher diet quality. Additional analyses are warranted to understand the biological mechanism for this association. Birth Defects Research 109:193-202, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…Of these, 123 studies met the inclusion criteria (figure 1). Fifty-eight studies11 24–80 concerning lifestyle and sociodemographic risk factors were included in the systematic review (online supplementary tables S1-S2). Twenty-nine studies11 29 32 34 37 38 40 41 46 48–51 53–55 59 60 62–66 69 73–75 79 80 were available for meta-analyses comprising 21 994 cases of gastroschisis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 123 studies met the inclusion criteria (figure 1). Fifty-eight studies11 24–80 concerning lifestyle and sociodemographic risk factors were included in the systematic review (online supplementary tables S1-S2). Twenty-nine studies11 29 32 34 37 38 40 41 46 48–51 53–55 59 60 62–66 69 73–75 79 80 were available for meta-analyses comprising 21 994 cases of gastroschisis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on lifestyle risk factors11 24–67 mainly investigated maternal smoking, illicit drug use, maternal alcohol consumption and maternal nutrition. Few studies investigated other maternal lifestyle habits (online supplementary table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced-fat varieties are best. [12].. Drinking more than 1000 ml of water per day) [13].. Snacks, cakes, pastries or sugar-sweetened drinks which high in saturated fat should be used less than five times a week and it is not a necessary part of a healthy diet and should be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates that were found to be statistically associated ( p < .05) with the outcome group and exposure using chi-square tests of independence or Fisher’s exact tests (if expected cell counts <5) were added separately to the exposure-only model; covariates that changed the cOR estimate by more than 10% were included in the adjusted model. Because a previous NBDPS study reported that increases in maternal water consumption were inversely associated with CL (Alman, Coffman, Siega-Riz, Luben, & National Birth Defects Prevention Study, 2017), we considered total maternal water consumption during the critical exposure period as a potential covariate in adjusted analyses. We observed that total maternal water consumption was not associated with any OFC outcome group using logistic regression analysis, and thus, it was not included in any adjusted models.…”
Section: Methodsmentioning
confidence: 99%